The Potential Role of Regulatory Genes (DNMT3A, HDAC5, and HDAC9) in Antipsychotic Treatment Response in South African Schizophrenia Patients - O’Connell, Kevin Sean; McGregor, Nathaniel Wade; Emsley, Robin; Seedat, Soraya; Warnich, Louise (Frontiers in Genetics, 2019)
Despite advances in pharmacogenetics, the majority of heritability for treatment response cannot be explained by common variation, suggesting that factors such as epigenetics may play a key role. Regulatory genes, such as those involved in DNA methylation and transcriptional repression, are therefore excellent candidates for investigating antipsychotic treatment response. This study explored the differential expression of regulatory genes between patients with schizophrenia (chronic and antipsychotic-naïve first-episode patients) and healthy controls in order to identify candidate genes for association with antipsychotic treatment response. Seven candidate differentially expressed genes were identified, and four variants within these genes were found to be significantly associated with treatment response (DNMT3A rs2304429, HDAC5 rs11079983, and HDAC9 rs1178119 and rs11764843). Further analyses revealed that two of these variants (rs2304429 and rs11079983) are predicted to alter the expression of specific genes (DNMT3A, ASB16, and ASB16-AS1) in brain regions previously implicated in schizophrenia and treatment response. These results may aid in the development of biomarkers for antipsychotic treatment response, as well as novel drug targets.